Inherited Cardiomyopathies and the Role of Mutations in Non-coding Regions of the Genome - Salman, Oday F.; El-Rayess, Hebah M.; Abi Khalil, Charbel; Nemer, Georges; Refaat, Marwan M. (Frontiers in Cardiovascular Medicine, 2018)
Cardiomyopathies (CMs) are a group of cardiac pathologies caused by an intrinsic defect within the myocardium. The relative contribution of genetic mutations in the pathogenesis of certain CMs, such as hypertrophic cardiomyopathy (HCM), arrythmogenic right/left ventricular cardiomyopathy (ARVC) and left ventricular non-compacted cardiomyopathy (LVNC) has been established in comparison to dilated cardiomyopathy (DCM) and restrictive cardiomyopathy (RCM). The aim of this article is to review mutations in the noncoding parts of the genome, namely, microRNA, promoter elements, enhancer/silencer elements, 3’/5’UTRs and introns, that are involved in the pathogenesis CMs. Additionally, we will explore the role of some long noncoding RNAs in the pathogenesis of CMs.